1999
DOI: 10.1046/j.1523-5378.1999.09034.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Aging of Helicobacter pylori: Changes in Morphology, Intracellular Composition and Surface Properties

Abstract: This study highlights several aspects of H. pylori aging in vitro and shows some of the differences that exist between bacillary and coccoid forms. This information is important for understanding the transmission and survival of H. pylori outside the human host, as the degradative changes in the intracellular composition and the surface properties shown here point to dead bacteria, and not to a viable but nonculturable form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
1
29
2
2
Order By: Relevance
“…Different chemicals as bismuth, as well as bile acids, antibiotics, temperature, nutritients, oxygen tension, starvation and aging are some examples [3,10,15,16,21,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different chemicals as bismuth, as well as bile acids, antibiotics, temperature, nutritients, oxygen tension, starvation and aging are some examples [3,10,15,16,21,25].…”
Section: Resultsmentioning
confidence: 99%
“…The role of the coccoid form in pathogenesis of H. pylori-associated gastritis has been disputed. Some authors consider the coccoid form as a degenerative or dead form of H. pylori [ 16,21,25], while others consider it as a resting but still metabolic active form [2, 3,12,22,29,321. The aim of this study was to demonstrate the conversion of spiral form of H. pylon to coccoid forms, and to show both degenerative and intact subcellar morphology suggesting that some of the coccoid bacteria may be viable.…”
Section: Introductionmentioning
confidence: 99%
“…Although usually spiral-shaped, the bacterium can appear as a rod, while coccoid shapes appear after prolonged in vitro culture or antibiotic treatment (342). These coccoids cannot be cultured in vitro and are thought to represent dead cells (342), although it has been suggested that coccoid forms may represent a viable, nonculturable state (162). The organism has 2 to 6 unipolar, sheathed flagella of approximately 3 m in length, which often carry a distinctive bulb at the end (481).…”
Section: Microbiology Of H Pylorimentioning
confidence: 99%
“…Lactose again prevented the bactericidal effect of Gal3. H. pylori bacteria are also known to change shape from spiral to coccoid under unfavorable conditions (35). As shown in Fig.…”
Section: Cd3mentioning
confidence: 99%